elles@centrepompidou Une nouvelle histoire ? - St-Gelais, Thérèse (Esse, 2010)
Commentaire de l'exposition elles@centre pompidou, Artistes femmes dans la collection du Musée national d’art moderne, centre de création industrielle qui eut lieu du 27 mai 2009 - 21 févr. 2011 au centre Pompidou à Paris.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; ressource en ligne; sofia; thématiques

Art et politique: nouvelles formes d'engagement artistique au Québec - Lamoureux, Ève (Éditions Écosociété, 2009)
Les artistes contemporains délaissent les grandes luttes communes, les partis politiques, et acceptent les subventions de l'État. Ils refusent les étiquettes et se moquent du mythe de l'artiste guidant le peuple. Quand l'oeuvre d'art devient fragments, mouvement, quand son sens est ouvert et dépend de l'expérience du spectateur, quelle est son action sur le monde? Peut-on encore croire à sa portée politique? Les nostalgiques pleurent la disparition de l'art engagé. Pour Ève Lamoureux, l'art engagé n'a jamais cédé; il résiste d'une autre manière, à un autre pouvoir, sur d'autres terrains. Exit la division entre l'art pour l'art et l'art au service d'une idée. Exit la conception avant-gardiste militante de l'art engagé. L'engagement actuel passe par une action micropolitique multiforme, une création soucieuse de l'Autre, à la fois autonome et collective, misant sur le processus et la participation. Ainsi, l'auteure nous montre de quelle façon l'art apporte une nouvelle définition de l'engagement politique. Cet essai analyse la démarche d'artistes québécois comme l'ATSA, BGL, Doyon/Demers, Danyèle Alain, Sylvie Cotton, Nicole Jolicoeur, Devora Neumark, Alain-Martin Richard, Jean-Claude St-Hilaire et Raphaëlle de Groot. En prolongeant, sur le plan théorique, des créations souvent performatives et éphémères (décors, manifestations, dialogues, oeuvres à compléter soi-même, etc.), ce livre les situe dans l'histoire récente de l'art et met en lumière leur dimension politique.
Keywords: 1900-1999; 2000 à aujourd'hui; amériques; approches et analyses; art engagé; arts; canada; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; régions géographiques; science politique; science politique et droit; thématiques

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques

With other eyes: looking at race and gender in visual culture - Bloom, Lisa (University of Minnesota Press, 1999)
Feminist and multiculturalist efforts to uncover the assumptions underpinning the production of art have transformed our understanding of visual culture. The field of art history, however, continues to downplay the race and gender politics informing its own interpretative practices. With Other Eyes brings together leading cultural theorists to demonstrate how feminist, postcolonial, and antiracist concerns can successfully and imaginatively be incorporated into the study of art. Rejecting strict definitions of “high art,” the contributors add photography, installation art, and film to the list of more conventional art forms to examine, for example, the construction of black femininity as influenced by Josephine Baker, Grace Jones, and the women depicted in Picasso’s Les Desmoiselles d’Avignon;the nationalist and class premises in nineteenth-century British Museum guidebooks; and the gendered visions of colonial discourse in advertisements for Ralph Lauren and the Body Shop.
Section: VIII-268 p. : illustrations ; 26 cm
Keywords: approches et analyses; arts; cours; discipline; féminisme décolonial; féminisme pop; har4610; histoire de l'art; histoire et politique; premier cycle; racisme; représentation des femme*; systèmes d'oppressions; thématiques

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis

The Amazing decade: women and performance art in America : 1970-1980 - Roth, Moira; Jacob, Mary Jane; Roth, Moira (Astro Artz., 1983)
"This book is a detailed study of the powerful and innovative role women artists played in the development and expansion of performance art. This hybrid art form, which combines the visual arts with ingredients drawn from experimental dance, theater, music, and poetry, emerged in the late 1960's at the same time as the women's movement. Many women artists turned to performance art in order to translate and capture visually the concerns, demands and visions of the women's movement; thus women led the way in performance art's explorations of autobiography, ritual, mass spectacle and the creation of characters and personae. The Amazing Decade, edited by Moira Roth, with an introduction by Mary Jan Jacob, culls the best from women's performance history, highlighting pivotal works, chronicling changes and projecting future directions: the book contains a major essay by Roth on the history and character of women's performance art; individual profiles on thirty-seven artists and collectives; an extensive bibliography; and a year-by-year chronology from 1956 onward in which women's performance art is set in the context of history and the women's movement. Profusely illustrated, The Amazing Decade is an indispensable reference book and an invaluable teaching tool"–
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis